Hubungan Pendidikan Dan Pekerjaan Dengan Kualitas Hidup Gay, Transgender, dan LSL - Resati Nando Panonsih; Arif Effendi; Ika Artini; Putri Eka Permata (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Gay, Transgender dan Men Who Have Seks With Men are individuals who are prone to problem both in health and in the environment such as education and work that will disrupt their lives and will have an impact on their quality of life. The study aim to know the relationship between education and occupation with the quality of life to the Gay, Transgender and MSM in Bandar Lampung 2019. The research using analytic survey with cross-sectional approach. The type of data obtained is primary data. The method of collecting data is by distributing questionnaires WHOQOL-BREF whose results will be categorized. This research was conducted from September to November 2019. In this research, the samples taken included all member of Gaya Lentera Muda organization with a total of 35 people, taken with total sampling technique. The report for quality of gay, transgender and MSM in Bandar Lampung who has middle education mostly have mild quality of life of 12 subjects (63,2%) and the subjects who have occupation mostly have mild quality of life of 12 subject (66,7%). The final results showed that there is a meaningful relationship between education and occupation with quality of life to gay, transgender and MSM in Bandar Lampung 2019 (p-value = 0,003 dan p-value = 0,414). The higher the level of education and the person has a working status, the higher the quality of life.